1995
DOI: 10.2175/106143095x133383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermented wastes on denitrification in activated sludge

Abstract: ABSTRACf: Fermented organic wastes were investigated as electron donors for denitrification in activated sludge. Fermentation of primary domestic wastewater sludge improved denitrification rates in nonacclimated activated sludge, whereas fermentation of wastewater had no effect. In both acclimated and nonacclimated activated sludges, higher denitrification rates were obtained with fermented sludges (from domestic wastewater or swine waste) than with either methanol or acetate. Methanol was equivalent to acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…Although the literature is somewhat contradictory, it has been observed that methanol requires an acclimation period prior to achieving the denitrification rates consistent with other carbon sources, perhaps more due to the establishment of a new population of methylotrophic C1 degrading denitrifying bacteria than acclimation (Kang et al 1992;Lee et al 1995;Regan et al 1998). There is also recent evidence suggesting that methanol utilization kinetics may be significantly slower than previously thought (significantly slower than ethanol) and that low temperature effects may be more pronounced (higher Arrhenius u value) .…”
Section: Alternative Carbon Sourcesmentioning
confidence: 98%
“…Although the literature is somewhat contradictory, it has been observed that methanol requires an acclimation period prior to achieving the denitrification rates consistent with other carbon sources, perhaps more due to the establishment of a new population of methylotrophic C1 degrading denitrifying bacteria than acclimation (Kang et al 1992;Lee et al 1995;Regan et al 1998). There is also recent evidence suggesting that methanol utilization kinetics may be significantly slower than previously thought (significantly slower than ethanol) and that low temperature effects may be more pronounced (higher Arrhenius u value) .…”
Section: Alternative Carbon Sourcesmentioning
confidence: 98%
“…for acetate (Carrera et al, 2003) and 0.077 (Peng et al, 2007), 0.17 (Carrera et al, 2003), and 0.29 g NO 3 2 -N/g VSS?d (Lee et al, 1995) for methanol.…”
Section: Figure 1-comparison Of Nomentioning
confidence: 95%
“…Methanol storage and usage represents a health and safety concern due operator exposure and flammability (methanol burns without a visible flame). Although the literature is somewhat contradictory, it has been observed that methanol requires an acclimation period prior to achieving the denitrification rates consistent with other carbon sources, perhaps more due to the establishment of a new population of methylotrophic C1 degrading denitrifying bacteria than acclimation (Kang et al, 1992;Lee et al, 1995;Regan et al, 1998). There is also recent evidence suggesting that methanol utilization kinetics may be significantly slower than previously thought (significantly slower than ethanol) and that low temperature effects may be more pronounced (higher Arrhenius θ value) (Mokhayeri et al, 2006).…”
Section: Alternative Carbon Sourcesmentioning
confidence: 99%